Association of MEOX2 polymorphism with nonsyndromic cleft palate only in a Vietnamese population. (28th November 2017) - Tran, Duy L.; Imura, Hideto; Mori, Akihiro; Suzuki, Satoshi; Niimi, Teruyuki; Ono, Maya; Sakuma, Chisato; Nakahara, Shinichi; Nguyen, Tham T.H.; Pham, Phuong T.; Hoang, Viet; Tran, Van T.T.; et al.
ABSTRACT: To evaluate the association between the single nucleotide polymorphism (SNP) rs227493 in the MEOX2 gene and nonsyndromic cleft palate only, this research was conducted as a case–control study by comparing a nonsyndromic cleft palate only group with an independent, healthy, and unaffected control group who were both examined by specialists. Based on clinical examination and medical records, we analyzed a total of 570 DNA samples, including 277 cases and 293 controls, which were extracted from dry blood spot samples collected from both the Odonto and Maxillofacial Hospital in Ho Chi Minh City and Nguyen Dinh Chieu Hospital in Ben Tre province, respectively. The standard procedures of genotyping the specific SNP (rs2237493) for MEOX2 were performed on a StepOne Realtime PCR system with TaqMan SNP Genotyping Assays. Significant statistical differences were observed in allelic frequencies (allele T and allele G) between the non‐syndromic cleft palate only and control groups in female subjects, with an allelic odds ratio of 1.455 (95% confidence interval: 1.026–2.064) and P  < 0.05. These study findings suggest that nonsyndromic isolated cleft palate might be influenced by variation of MEOX2, especially SNP rs2237493 in Vietnamese females.